School Heads’ Leadership Styles: Impact on Organizational Innovativeness and Performance of Public Elementary Schools in the New Normal - Felix M. Diano Jr.; Jamera S. Calbi (Randwick International of Education and Linguistics Science Journal, 2024)
This study determines the impact of school heads’ leadership styles on organizational innovativeness and performance of public elementary schools in Cebu City Division in the new normal. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized to investigate the linear causal relationships among the variables. Moreover, the study found that transformational leadership of the school head is not related to the organizational innovativeness of the school. However, transactional, and instrumental leadership influence the organizational innovativeness of the schools. On one hand, participative leadership only promotes product innovation, while supportive leadership augments management innovation directly. Lastly, product innovation of the school impacts the school’s performance.